Composite elastomeric polyurethane scaffolds incorporating small intestinal submucosa for soft tissue engineering. (1st September 2017) - Da, Lincui; Gong, Mei; Chen, Anjing; Zhang, Yi; Huang, Yizhou; Guo, Zhijun; Li, Shengfu; Li-Ling, Jesse; Zhang, Li; Xie, Huiqi
Graphical abstract: Abstract: Although soft tissue replacement has been clinically successful in many cases, the corresponding procedure has many limitations including the lack of resilience and mechanical integrity, significant donor-site morbidity, volume loss with time, and fibrous capsular contracture. These disadvantages can be alleviated by utilizing bio-absorbable scaffolds with high resilience and large strain, which are capable of stimulating natural tissue regeneration. Hence, the chemically crosslinked tridimensional scaffolds obtained by incorporating water-based polyurethane (PU) (which was synthesized from polytetramethylene ether glycol, isophorone diisocyanate, and 2, 2-bis(hydroxymethyl) butyric acid) into a bioactive extracellular matrix consisting of small intestinal submucosa (SIS) have been tested in this study to develop a new approach for soft tissue engineering. After characterizing the structure and properties of the produced PU/SIS composites, the strength, Young's modulus, and resilience of wet PU/SIS samples were compared with those of crosslinked PU. In addition, the fabricated specimens were investigated using human umbilical vein endothelial cells to evaluate their ability to enhance cell attachment and proliferation. As a result, the synthesized PU/SIS samples exhibited high resilience and were capable of enhancing cell viability with no evidence of cytotoxicity. Subcutaneous implantation in animals and the subsequent testing conducted after 2, 4, and 8 weeks indicated that sound implant integration and vascularization occurred inside the PU/SIS composites, while the presence of SIS promoted cell infiltration, angiogenesis, and ultimately tissue regeneration. The obtained results revealed that the produced PU/SIS composites were characterized by high bioactivity and resilience, and, therefore, could be used for soft tissue engineering applications. Statement of Significance: Hybrid composites containing synthetic polymers with high mechanical strength and naturally derived components, which create a bio-mimetic environment, are one of the most promising biomaterials. Although synthetic polymer/ECM composites have been previously used for soft tissue repair, their resilience properties were not investigated in sufficient detail, while the development of elastic composites composed of synthetic polymers and ECMs in nontoxic aqueous solutions remains a rather challenging task. In this study, porous PU/SIS composites were fabricated in a non-toxic manner; the obtained materials exhibited sufficient mechanical support, which promote cell growth, angiogenesis, and tissue regeneration. The described method can be adapted for the development of scaffolds with various acellular matrices and subsequently used during the restoration of particular types of tissue.